PENGGUNAAN PASIR WEOL SEBAGAI BAHAN CAMPURAN MORTAR DAN BETON STRUKTURAL - Kadimas, Irenius O.R; Pah, Jusuf J.S.; Bella, Rosmiyati A. (Jurnal Teknik Sipil, 2017)
Concrete is formed from a mixture of water, cement, sand and coarse aggregate. The quality of sand affects the quality of the concrete. Weol sand is aggregate in the subdistrict Ruteng, Manggarai district, which is used by people for mortar and non-structural concrete. This is because the location of which is closer than the other sand. This study aims to determine the compressive strength of mortar and concrete using Weol sand.The method of implementation refers to the SNI 03-2834-2000 (BSN 2000) about Manufacturing Process Plan Mixture for Normal Concrete and SNI 03-6825-2002 (BSN 2002b) about The Test Method of Compressive Strength Portland Cement Mortar. The mortar cube has size 5x5x5 with composition 1PC: 2Psr, 1PC: 4Psr, 1PC: 6Psr and 1PC: 8Psr. The diameter and high of cylindrical concrete is 15 cms and 30 cms. Mortar compressive strength testing performed at 3 days, 7 days, 14 days and 28 days while the concrete at 7 days, 14 days and 28 days.The test results show that the compressive strength of mortar using Weol sand for each composition and the compressive strength of concrete using Weol sand for each quality plan is larger than mortar and concrete using Takari sand.